Sector Surcharges for Temporary Agency Workers in Germany: A Way Out of the Low-Wage Sector? - Alexander Spermann (Institute for the Study of Labor (IZA), 2013)
Sector-specific surcharge collective labor agreements between the bargaining partners in the staffing industry allow for a reduction of wage gaps between agency workers and permanent staff in case of long-term job assignments to user companies. Surcharges up to 50% after a surcharge-free period between four and six weeks close the wage gap in nine industries for the temporary work agencies. The paper summarizes the development that lead to these collective labor agreements and analyzes repercussions on potential upward mobility of previously unemployed who start their career as agency workers in the low-wage sector. Furthermore, it highlights the interaction with the basic income scheme, documents new evidence on sustainable employment and draws conclusions for the precarious work discussion. It turns out that these new surcharges allow agency workers to leave the low-wage sector in case of longer job assignment in the core user company industries such as the metal and electrical industry.
Keywords: I2; J2; J4; 330; temporary agency work; staffing industry; collective labor agreement; low-wage sector; precarious work; Leiharbeit; Lohnpolitik; Niedriglohn; Wirkungsanalyse; Arbeitsmarktintegration; Deutschland